Effects of Forest Cover Change on Flood Characteristics in the Upper Citarum Watershed - Bambang Dwi Dasanto; Bambang Pramudya; Rizaldi Boer; Yuli Suharnoto (Jurnal Manajemen Hutan Tropika, 2014)
Information on the effect of forest cover changes on streamflow (river discharge) in large-scale catchment is important to be studied. The rate of forest cover change in the Upper Citarum Watershed as a large-scale catchment is high enough to drive streamflow change, such as increase of discharge level, or flood volume. Within the research area, flood would occur when the volume of streamflow exceeded the canal capacity and inundated areas that were normally dry. Therefore, this research focused on identifying the effects of forest cover change on flood events and its distribution. The research consisted of 2 main stages; firstly, building geometric data of river and performing frequency analysis of historical and scenario discharges using an approach of probability distribution; and, secondly, flood inundation mapping using HEC-RAS model. The results showed that forest reduction have affected water yield in the downstream of Upper Citarum Watershed. In each return period, this reduction have increased river discharge level and affected the spread of flooded areas. In 2-year return period, the extent of flood as an impact of forest reduction was estimated to decrease slowly. However, in the return period of more than 2 years, the spread of flooded areas increased sharply. These proved that forest cover reduction would always increase the discharge value, but it did not always expand the inundated area.